2012
DOI: 10.1186/1743-8977-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of ambient particulate air pollution and biomarkers of inflammation, coagulation and homocysteine in healthy adults: A prospective panel study

Abstract: BackgroundAmbient air pollution has been associated with activation of systemic inflammation and hypercoagulability and increased plasma homocysteine, but the chemical constituents behind the association are not well understood. We examined the relations of various chemical constituents of fine particles (PM2.5) and biomarkers of inflammation, coagulation and homocysteine in the context of traffic-related air pollution.MethodsA panel of 40 healthy college students underwent biweekly blood collection for 12 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(86 citation statements)
references
References 56 publications
6
77
1
2
Order By: Relevance
“…A 7-day intervention study with air filtration in the homes of a wood smoke impacted area found an association between the indoor concentration of PM 2.5 and CRP (Allen et al, 2011), whereas three other studies with air filtration in Copenhagen, Denmark, showed no effect on CRP (Brauner et al, 2008a,b;Karottki et al, 2013). There seem to be mixed results with regard to associations between ambient or individual-level PM 2.5 exposure and CRP; some studies have shown positive associations (Huttunen et al, 2012;Zhao et al, 2013), whereas other studies have reported no effect on CRP levels in the circulation (Liu et al, 2009;Ruckerl et al, 2007a;Strak et al, 2013;Wu et al, 2012). A review concluded that there was an association between air pollution exposure and elevated levels of CRP in children, whereas there were inconsistent results on healthy adults (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…A 7-day intervention study with air filtration in the homes of a wood smoke impacted area found an association between the indoor concentration of PM 2.5 and CRP (Allen et al, 2011), whereas three other studies with air filtration in Copenhagen, Denmark, showed no effect on CRP (Brauner et al, 2008a,b;Karottki et al, 2013). There seem to be mixed results with regard to associations between ambient or individual-level PM 2.5 exposure and CRP; some studies have shown positive associations (Huttunen et al, 2012;Zhao et al, 2013), whereas other studies have reported no effect on CRP levels in the circulation (Liu et al, 2009;Ruckerl et al, 2007a;Strak et al, 2013;Wu et al, 2012). A review concluded that there was an association between air pollution exposure and elevated levels of CRP in children, whereas there were inconsistent results on healthy adults (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Wu et al (2012) observed a 3.9% [0.3, 7.6%] increase in fibrinogen in association with elevated 24 h-averages in PM 2.5 Fe. This association strengthened (5.9% [0.2;12.0%]) when including PM 2.5 in the model.…”
Section: Elemental Components Of Pm and Healthmentioning
confidence: 93%
“…To date, the effects of chemical components of PM on inflammatory blood markers were only assessed in a panel study (Wu et al, 2012) and in a semi-experimental investigation (Strak et al, 2013). Wu et al (2012) observed a 3.9% [0.3, 7.6%] increase in fibrinogen in association with elevated 24 h-averages in PM 2.5 Fe.…”
Section: Elemental Components Of Pm and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The panel study used a repeated-measure study protocol to quantify short-term air pollution exposures and health observations over time in order to facilitate assessment of the health effects of changes in exposure over time (Janes et al, 2008). Detailed information on the study design and participant recruitment could be found elsewhere (Wu et al, 2012(Wu et al, , 2013. The BIT has 2 campuses about 30 km apart, one (BIT Liangxiang campus) is located in the southwest suburban area and the other one (BIT main campus) is located in the northern urban area of Beijing.…”
Section: Study Participants and Designmentioning
confidence: 99%